2000
DOI: 10.1002/(sici)1098-2744(200003)27:3<184::aid-mc5>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Activation of theMN/CA9 gene is associated with hypomethylation in human renal cell carcinoma cell lines

Abstract: The MN/CA9 (G250) gene expressed in the normal alimentary tract in a tissue-specific manner is often activated in renal cell carcinomas. To cast light on the activation mechanism, we examined the methylation status of this gene in seven human renal cell carcinoma cell lines (SKRC-01, -06, -10, -12, -14, -44, and -59) and three normal kidney tissue samples by using the bisulfite genomic sequencing protocol. CpG methylation was measured at seven locations in the MN/CA9 5' region. MN/CA9 transcripts were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
(20 reference statements)
2
13
1
Order By: Relevance
“…To address the former possibility, we further studied the methylation status of the CA9 gene in RCC cell lines. The results clearly showed that CA IX expression was down-regulated by methylation in the 5' region of the CA9 gene as previously reported (Cho et al 2000). Although the biological activity and expression levels of normal VHL in RCC cell lines are still unknown, the results obtained in this study indicate CA IX expression is under the dual-regulation by methylation on its gene and VHL.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To address the former possibility, we further studied the methylation status of the CA9 gene in RCC cell lines. The results clearly showed that CA IX expression was down-regulated by methylation in the 5' region of the CA9 gene as previously reported (Cho et al 2000). Although the biological activity and expression levels of normal VHL in RCC cell lines are still unknown, the results obtained in this study indicate CA IX expression is under the dual-regulation by methylation on its gene and VHL.…”
Section: Discussionsupporting
confidence: 88%
“…DNA was resuspended in water and stored at )20°C until later use. Sequencing of the bisulfite-treated DNA was carried out to investigate the CpG methylation status at the 5'-end of the coding region of the CA9 gene as previously reported Cho et al 2000). DNA fragments (nt -142 to +267) were amplified using the nested PCR technique.…”
Section: Methylation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, aberrant methylation of CAIX has been demonstrated in renal cell carcinoma. [48][49][50] Supporting this, we also found indirect evidence for CAIX epigenetic regulation in this study with the re-expression of CAIX protein in the OVCA432 and UPN251 following chromatin modifying treatment with TSA.…”
Section: Discussionsupporting
confidence: 82%
“…This loss of methylation has important consequences. It can lead to increased expression of dominantly acting oncogenes, such as R-ras in gastrointestinal cancer (Nishigaki et al 2005) and cyclinD2 and maspin in pancreatic cancer (Cho et al 2000;Akiyama et al 2003). This hypomethylation-associated gene activation received comparatively less attention than gene silencing until recently, but it is increasingly clear that these changes are as important as those associated with gene silencing.…”
mentioning
confidence: 99%